A mobile game as a support tool for children with severe difficulties in reading and spelling. (2nd June 2020) - Ronimus, Miia; Eklund, Kenneth; Westerholm, Jari; Ketonen, Ritva; Lyytinen, Heikki
Abstract: We used a randomized controlled trial to investigate if a mobile game, GraphoLearn (GL), could effectively support the learning of first graders ( N = 70), who have severe difficulties in reading and spelling. We studied the effects of two versions of the game: GL Reading, which focused on training letter‐sound correspondence and word reading; and GL Spelling, which included additional training in phonological skills and spelling. During the spring of first grade, the children trained with tablet computers which they could carry with them during the six‐week intervention. The average exposure time to training was 5 hr 44 min. The results revealed no differences in the development of reading or spelling skills between GL players and the control group. However, pre‐training self‐efficacy moderated the effect among GL Reading players: children with high self‐efficacy developed more than the control group in word reading fluency, whereas children with low self‐efficacy developed less than the control group in spelling. Lay Description: What is already known: Serious games can support children's reading achievement, but less is known about their effects in mobile learning. GraphoLearn (GL) is a serious game designed to support reading acquisition, but previous studies suggest its effect on word‐level reading is limited. Explicit training of phonological skills and spelling could facilitate transfer to word reading. Self‐efficacy predicts persistence and effort in achievement situations but its role in mobile game‐based learning is not well known. What this paper adds: A randomized controlled trial was used to study if mobile game‐based learning supports children with reading difficulties. A new GL version, training phonological and spelling skills, had no effect on the development of reading and spelling skills. Children with high self‐efficacy benefited from training with the standard GL. Implications for practitioners: When using mobile games as support tools, close attention should be paid to learner characteristics and game design. Children with high self‐efficacy may be better able to regulate their behaviour during independent training with mobile games, leading to better learning outcomes.